Análise da vulnerabilidade da rede viária urbana na acessibilidade do transporte urbano de cargas sob a ótica da emissão de CO2 - Santos, João Evangelista Dantas dos (2024)
Urban mobility in large cities faces significant challenges due to congestion, which impacts the economy, the environment, and public health, exacerbated by rapid urbanization. In Brazil, urban freight transport has been the focus of public policies for its contribution to CO2 emissions. Factors such as the vulnerability of the road network, intensified by floods and accidents, compromise the operational efficiency of this sector, highlighting the need to balance operational and environmental costs in sustainable transport. Proper urban planning and efficient vehicle flow management are essential to mitigate congestion and reduce pollution, demanding an integrated approach that considers economic, spatial, and environmental aspects. This study aims to analyze the vulnerability of the urban road network and its influence on the accessibility of urban freight transport, focusing on CO2 emissions. To this end, studies will be conducted involving: the analysis of the impacts of road network topological characteristics on route choice; the investigation of how these configurations affect the vulnerability and accessibility of freight transport; and the evaluation of the impact of road network vulnerability on CO2 emissions associated with urban freight transport. Chapter 2 identifies factors that increase the vulnerability of the road network for freight transport. Results indicate that poor infrastructure, congestion, and circulation restrictions are the main vulnerability factors, with lack of maintenance and proper planning being critical for safety and efficiency. Chapter 3 analyzes how vulnerability affects road network accessibility, showing that vulnerable areas have reduced accessibility, resulting in longer travel times and operational costs. It is suggested that investments in infrastructure and traffic management policies can improve accessibility. Chapter 4 examines the relationship between accessibility and vulnerability of the urban network, considering different topological configurations and impedances for freight vehicles, evaluating the impact on CO2 emissions. Adapting an integrated indicator of emissions and travel time provides a detailed analysis. Results are fundamental for urban planning, showing that irregular road networks are more vulnerable to disruptions, leading to chaotic traffic redistribution, while regular networks maintain temporary balance but develop new vulnerabilities in the long term. The analysis of vulnerability and its consequences on CO2 emissions highlights the importance of restrictive measures to promote more sustainable and efficient urban freight transport systems.